Upaya Meningkatkan Regulasi Diri Pada Mahasiswa - & Jenni Marlina, emanuel haru, Fidelis Den (Jurnal Alternatif Wacana Ilmiah Interkultural, 2023)
Abstract Self-regulation is one of the abilities that everyone must have in order to achieve goals based on the desired standards. This article aims to discuss self-regulation of a student at college as one of the abilities that must be possessed in order to achieve his/her learning goals. There are several problem formulations presented in this article. First, what is self-regulation? Second, what are the dimensions of self-regulation? Third, what factors influence self-regulation of a student at a college? Fourth, what efforts are being made to increase self-regulation of a student at a college? By using literature study methods and reviewing research findings regarding self-regulation, the author concludes as follows. First, self-regulation is an individual's ability to organize, direct and control themselves so that they remain on the goals they want to achieve and in accordance with the desired standards. Second, aspects of self-regulation are: metacognitive, motivation and positive action. Third, the factors that influence students' self-regulation are internal and external factors. Internal factors are motivation, having academic goals, self-adaptation abilities and previous experience. While external factors are social support from peers, family (parents) and lecturers. Fourth, efforts to increase self-regulation of a student at a college are: making a regular schedule, setting clear goals, applying management techniques, avoiding procrastination and forming good study habits. Regulasi diri merupakan salah satu kapasitas yang harus dimiliki setiap orang agar dapat mencapai tujuan sesuai standar yang diinginkan. Artikel ini bertujuan untuk membahas regulasi diri mahasiswa di perguruan tinggi sebagai salah satu kapasitas yang harus dimiliki guna mencapai tujuan belajarnya. Ada beberapa rumusan masalah yang disajikan dalam artikel ini. Pertama, apa yang dimaksudkan dengan regulasi diri? Kedua, apa saja dimensi regulasi diri? Ketiga, faktor-faktor apa saja yang mempengaruhi regulasi diri seorang mahasiswa di suatu perguruan tinggi? Keempat, upaya-upaya apa saja yang dilakukan untuk meningkatkan regulasi diri mahasiswa di suatu perguruan tinggi? Dengan menggunakan metode studi literatur dan mengkaji temuan penelitian mengenai regulasi diri, disimpulkan sebagai berikut. Pertama, regulasi diri merupakan kemampuan individu dalam mengatur, mengarahkan dan mengendalikan dirinya agar tetap pada tujuan yang ingin dicapainya dan sesuai dengan standar yang diinginkan. Kedua, aspek-aspek regulasi diri yaitu: metakognitif, motivasi dan tindakan positif. Ketiga, faktor-faktor yang mempengaruhi regulasi diri mahasiswa adalah faktor internal dan eksternal. Faktor internal adalah motivasi, memiliki tujuan akademik, kemampuan adaptasi diri dan pengalaman sebelumnya. Sedangkan faktor eksternal adalah dukungan sosial dari teman sebaya, keluarga (orang tua) dan dosen. Keempat, upaya-upaya untuk meningkatkan regulasi diri seorang mahasiswa di perguruan tinggi adalah: membuat jadwal yang teratur, menetapkan tujuan yang jelas, menerapkan teknik manajemen, menghindari prokrastinasi dan membentuk kebiasaan belajar yang baik.